Waste Heat Recovery From The Exhaust Of Natural Aspirated Engine - Herawan, Safarudin Gazali; Rohhaizan, Abdul Hakim; Ismail, Ahmad Faris (2012)
The utilization of exhaust waste heat is now well known and the basic of many combined cooling, heating, and power installations. Heat recovery from automotive engines has been predominantly for turbo-charging or others such as cabin heating, thermoelectric, and air conditioning. The exhaust gases from such installations represent a significant amount of thermal energy that traditionally has been used for combined heat and power applications. This paper explores the theoretical performance and simulation of natural aspirated spark ignition engine model of 1.6 L, which is occupied with waste heat recovery mechanism (WHRM). Mathematical model and simulation test results suggest that the concept is PFI thermodynamically feasible and could significantly enhance system performance depending on the load applied on the engine. However, the experimental test should be conducted to validate the simulation results as for scalability and reliability that require further investigation.